Problem Based Learning dan GeoGebra 3D Calculator: Pengaruhnya terhadap Kemampuan Spasial Siswa - Akbar, Risal; Mattoliang, Lisnasari Andi; Baharuddin, Baharuddin; Majid, Ahmad Farham; Abrar, Andi Ika Prasasti (Faculty of Tarbiyah and Teacher Training, 2025)
Students' spatial abilities often do not receive optimal development in the learning process, even though they are crucial aspects in mathematics. This study aims to test differences in the effectiveness of the Problem Based Learning (PBL) model integrated with the GeoGebra 3D Calculator on students' spatial abilities, compared to the PBL model without the media. This quasi-experimental study used a Randomized Posttest-Only Control Group design involving 65 eighth-grade students at MTs Madani Alauddin, who were divided into an experimental class (n=31) and a control class (n=34). Spatial ability data were collected through a descriptive posttest instrument. The results showed that the experimental class's average spatial ability (73.62) was significantly higher than that of the control class (69.17). The independent sample t-test confirmed a significant difference, meaning that the PBL model treatment with GeoGebra 3D Calculator was more effective. It was concluded that the application of the PBL model combined with the GeoGebra 3D Calculator had a positive and significant effect on improving students' spatial abilities, while emphasizing the important role of interactive visual media in facilitating understanding of geometric spatial concepts.